IMPLEMENTASI PEMENUHAN HAK ANAK KORBAN KEKERASAN SEKSUAL DALAM PERSPEKTIF VIKTIMOLOGI - Anastassia Aurel (2023)
In handling cases of sexual violence against children, child victims often do not get their rights as victims of violence. There are two laws and regulations that can be used in cases of sexual violence, namely the Law on Child Protection and the Law on Crimes of Sexual Violence. These two laws have very significant differences in arrangements regarding the fulfillment of the rights of children who are victims of sexual violence. The Witness and Victim Protection Agency (LPSK) within its authority is mandated to provide protection and fulfillment of the rights of witnesses and victims. However, obstacles were found so that the LPSK was still not optimal in carrying out its authority in providing protection and fulfilling the rights of child witnesses and victims. The purpose of this study was to identify, explain and analyze how the rights of children victims of sexual violence are implemented from a victimological perspective and the obstacles encountered in fulfilling the rights of children victims of sexual violence from the victim's perspective. The method used in this study is normative juridical using a statute approach, case approach, and conceptual approach. Data collection techniques in this study used library research. Based on the results of the study, it was concluded that in the TPKS Law, the rights granted to children of sexual violence victims cover more rights of victims as a whole and the LPSK has not been optimal in exercising its authority in providing protection and fulfilling the rights of child victims of sexual violence.